A Critical Discourse Analysis of the Language on the Homepage of Selected Universities in Ghana - Dankwa Boateng, Oliver; Chinwendu Israel, Peace (International Journal of Arts, Languages, Linguistics and Literary Studies, 2022)
This study examined the language of websites of universities in Ghana and how it is used to represent the institutions. It was based on Fairclough’s (1993; 1995a, 2001) approach to Critical Discourse Analysis. The first six premier universities in Ghana were purposively selected for this study, namely, University of Ghana, University of Cape Coast, Kwame Nkrumah University of Science and Technology, University of Education, Winneba, University for Development Studies and Valley View University. The findings revealed the following: the universities build their institutional identities on their Homepages through texts and visuals; the universities express their power to determine what to present to viewers of the website; the language on the websites are institutional centred; the universities use similar texts that serve as promotional discourse; the websites contained elements that present the universities with peculiar African (Ghanaian) characteristics. The findings have implication for pedagogy, theory and practice as it enables universities in Ghana to know how they are represented on their institutional websites in order to improve their marketing strategies especially toward their visibility on the global front, better positioning on the international ranking and the attraction of international students.